Opportunities for organ donor intervention research : saving lives by improving the quality and quantity of organs for transplantation - Liverman, Catharyn T.; Domnitz, Sarah Brooke; Childress, James F. (Consensus study report., 2017)
The organ donation and transplantation system strives to honor the gift of donated organs by fully using those organs to save and improve the quality of the lives of their recipients. However, there are not enough donated organs to meet the demand and some donated organs may not be recovered, some recovered organs may not be transplanted, and some transplanted organs may not function adequately. Organ donor intervention research can test and assess interventions (e.g., medications, devices, and donor management protocols) to maintain or improve organ quality prior to, during, and following transplantation. The intervention is administered either while the organ is still in the deceased donor or after it is recovered from the donor but before it is transplanted into a recipient. Organ donor intervention research presents new challenges to the organ donation and transplantation community because of ethical questions about who should be considered a human subject in a research study, whose permission and oversight are needed, and how to ensure that such research does not threaten the equitable distribution of a scarce and valuable resource. Opportunities for Organ Donor Intervention Research focuses on the ethical, legal, regulatory, policy, and organizational issues relevant to the conduct of research in the United States involving deceased organ donors. This report provides recommendations for how to conduct organ donor intervention research in a manner that maintains high ethical standards, that ensures dignity and respect for deceased organ donors and their families, that provides transparency and information for transplant candidates who might receive a research organ, and that supports and sustains the public's trust in the process of organ donation and transplantation.